Determinants of child nutrition in Nigeria (2010)
The importance of nutrition for an individual's well-being cannot be over emphasised because of its link to child poverty and development of adult human capital. This paper examines the effects of household resources and community-level variables on child nutrition (as indicated by the anthropometric measure of height for age). The data used for this study are drawn from the 1999 Multiple Indicator Cluster Survey in Nigeria. The survey covers the whole country and questionnaires were administered to 18,300 households. We employ a model of nutrition status derived from the maximisation of household utility function. The model estimates the effects of household resources, parental education as well as community-level variables on child health status. We also explore the issue of nonlinearities in parental education as well as interaction between some community variables and parental education. Our results suggest significant relationships between household resources, community factors and child health.